Constraints on parallel activation in bilingual spoken language processing: examining proficiency and lexical status using eye-tracking. - Blumenfeld HK; Marian V (Language & Cognitive Processes, 2007)
During spoken word-recognition, bilinguals have been shown to access their two languages simultaneously. The present study examined effects of language proficiency and lexical status on parallel language activation. Language proficiency was manipulated by testing German-native and English-native bilingual speakers of German and English. Lexical status was manipulated by presenting target words that either overlapped in form across translation equivalents (cognate words) or did not overlap in form across translation equivalents (English-specific words). Participants identified targets (such as hen) from picture-displays that also included similar-sounding German competitor words (such as Hemd, 'shirt'). Eye-movements to German competitors were used to index co-activation of German. Results showed that both bilingual groups co-activated German while processing cognate targets; however, only German-native bilinguals co-activated German while processing English-specific targets. These findings indicate that high language proficiency and cognate status boost parallel language activation in bilinguals.